Child Labor Protection Based on Indonesian Manpower Act and Human Rights Principle - Ridwan Arifin; Rodiyah Rodiyah; Aprilia Putri Adiningsih (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
Child labor in many cases tends to experience various acts of crime and violence, even in the violation of their human rights, such as human trafficking and exploitation. Child labor has been regulated in various laws and regulations, including the Manpower Act. This paper examines three important key issues, namely: first, the legal protection of child labor in Indonesia based on labor and human rights laws, second, an analysis of the child labor protection rules applicable in Indonesia, and third, the emergence of child labor (child labor) in Indonesia. This research is normative legal research, where the study is literature. However, field data on this study were obtained from various related previous research results, both print and online sources. This research emphasized that the prohibition of working or employing children has been regulated in the Manpower Act which is closely related to efforts to protect children’s rights, which are also guaranteed protection in Law Number 39 of 1999 concerning Human Rights (Human Rights Act). The principle of child protection not only stipulated on Human Rights Act, but also Indonesian Manpower Act and Indonesia Child Protection Act. However, weaknesses of Manpower Act do not expressly prohibit child labor. In certain occupations, child labor is still permitted on various conditions. But in fact, these requirements are very difficult to control so that many children’s rights are violated.